2020
DOI: 10.1111/os.12790
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Anteversion of Cup and Combined Anteversion for Total Hip Arthroplasty Using Lateral Approach

Abstract: Objective To determine the implant orientation, especially the combined anteversion measurements in total hip arthroplasty (THA) using lateral approach, and to compare with implant orientation using posterior‐lateral (P‐L) approach. The secondary goal was to identify the factors associated with implant orientation. Methods Five hundred and one patients (545 hips) who underwent primary THA with the modified Hardinge approach between January 2016 and November 2019 by one senior surgeon in our department in a ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…Using PP as a reference plane, 51.7% of THA patients on DLA and 39.3% of THA patients on PLA were inside the Lewinnek safe zone. 7 This DLA result is similar to the 52.9% distribution rate obtained by Li et al 19 but lower than that (57%) measured by Timothy et al 21 using CT. This difference may be due to the biological reasons for the different positions in CT and EOS examinations.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Using PP as a reference plane, 51.7% of THA patients on DLA and 39.3% of THA patients on PLA were inside the Lewinnek safe zone. 7 This DLA result is similar to the 52.9% distribution rate obtained by Li et al 19 but lower than that (57%) measured by Timothy et al 21 using CT. This difference may be due to the biological reasons for the different positions in CT and EOS examinations.…”
Section: Discussionsupporting
confidence: 84%
“…We also found that gender and femoral head diameter were factors influencing acetabular cup anteversion (Table 3). Hartel's study also showed that gender is a small but significant factor in acetabular cup anteversion in THA, 38 differing from previous studies 19 . This may be caused by chance, as there was no difference in patient gender or femoral head diameter.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations